If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (y + -2) = -4x + 4 Reorder the terms: (-2 + y) = -4x + 4 Remove parenthesis around (-2 + y) -2 + y = -4x + 4 Reorder the terms: -2 + y = 4 + -4x Solving -2 + y = 4 + -4x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + y = 4 + 2 + -4x Combine like terms: -2 + 2 = 0 0 + y = 4 + 2 + -4x y = 4 + 2 + -4x Combine like terms: 4 + 2 = 6 y = 6 + -4x Simplifying y = 6 + -4x
| -5=8(x-4)-5x | | (-3a)(2a)(-4a)= | | x+8=x^2+4x-7 | | 8v+2(v+2)=-36 | | -5+13=5b-8-4b | | c=.5mv | | c=1/2mv | | -4=6x+2(-4x) | | 2.5x+6y=480 | | 5n^2-2n+28=0 | | -b=4a+3c-p | | X^5-3x+2x=0 | | 2xy-5=9 | | y=5+-10x | | -10x=-12 | | 13x+29y=-23 | | 20m-7-2m=8m-2 | | 2.3m+1=1.3m+7 | | -2-2=4-2X+3X | | 1/2*x-5=10 | | Y=-3/8x-2 | | 7.34=2(3.14)r | | e^8x+3=19 | | 15*500= | | 43x+2=38 | | 4w+2-3w=7 | | -4(x-4)=-3(x-7)-4 | | 5+10-5*2+45+2x=400 | | 40X+(1.5X)(5)=661 | | 8p-19=-28+7p | | 15+4a^2=2a^3-5 | | 4r-13=-15+5r |